Pengembangan Soft Skills Siswa di SDN 64 Malaka Melalui Seminar Pendidikan: Tantangan Dan Peluang - ibrahim arifin; M.Ridwan Said Ahmad; Zainal Arifin; Andi Sadriani; Muh Rijal; Ilham Saputra (PT Ininnawa Paramacitra Edu, 2026)
Soft skills development at the elementary level, particularly at SDN 64 Malaka, is a crucial need to prepare students to adapt to the dynamic conditions of the digital age. Academic skills alone are no longer sufficient; students also require strong interpersonal skills. This activity aims to explore the process of developing students' soft skills through the integration and assistance of information technology. Specifically, the primary goal of this community service activity is to hone, guide, and enhance students' basic soft skills, such as communication, collaboration, problem-solving, and creativity, which will be invaluable for their future.This community service activity was implemented using a participatory approach at SDN 64 Malaka through educational seminars, interactive workshops, and direct mentoring. The use of educational and interactive technology media was also incorporated to facilitate understanding and engage students' learning more effectively. The results of this mentoring program revealed significant findings: students possess a wealth of hidden potential, but they have not had the appropriate channels or facilities to channel it. Through this technology-based approach, students appear to be more enthusiastic and confident in expressing themselves. The soft skills strengthening program has proven crucial in developing students with strong charact er and practical, applicable skills. It is hoped that schools and stakeholders will continue to integrate this technology - based soft skills training into daily learning activities in the future to facilitate and sustainably develop students' potential.